The Contegra conduit: Late outcomes in right ventricular outflow tract reconstruction - Anthony A Holmes; Steve Co; Derek G Human; Jacques G LeBlanc; Andrew IM Campbell (Wolters Kluwer Medknow Publications, 2012)
Objectives: To report the clinical outcomes (early death, late death, and rate of reintervention) and performance of the Contegra conduit as a right ventricle outflow tract implant and to determine the risk factors for early reintervention. Methods: Forty-nine Contegra conduits were implanted between January 2002 and June 2009. Data collection was retrospective. The mean age and follow-up duration of Contegra recipients was 3.5 ± 4.6 years and 4.2 ± 2.0 years, respectively. Results: There were three deaths (two early, one late), giving a survival rate of 93.9%. The rate of conduit-related reintervention was 19.6% and was most often due to distal conduit stenosis. Age at implantation of <3 months, receipt of a conduit of 12-16 mm diameter, and a diagnosis of truncus arteriosus were each significant contributors to the rate of reintervention. Conclusion: The Contegra is a cost-effective and readily available solution. However, there is a limited range of larger calibers, which means that the homograft conduit (>22 mm) remains the first choice of implant in older children. The rates of reintervention are significantly higher with a diagnosis of truncus arteriosus, age at implantation of <3 months, and implantation of conduits sized 12-16 mm.